Vulnerability of Parkia biglobosa, Vitellaria paradoxa and Vitex doniana to climate change: wild indigenous agroforestry species in Benin - Kakpo, Angeline; Vodounnon, Mahunan José; AGBANGBA, Codjo Emile; Glèlè kakaï, Romain (My University, 2023)
Climate change is a major threat to biodiversity, with global greenhouse gas emissions exceeding the Paris Agreement, which has a signifcant impact on the distribution of species at risk of facing extinction. Thus, predicting climate change's infuence on species distribution is crucial. In Sub-Saharan Africa, particularly in Benin, some useful plants such as Parkia biglobosa, Vitex doniana, and Vitellaria paradoxa contribute greatly to improving socio-economic standards. However, they are subjected to overexploitation and climate change, which potentially could lead to their extinction. To predict the habitat suitability of these native agroforestry species for their conservation and cultivation, we assessed the best-performing algorithm among Maximum Entropy, Random Forest, Support Vector Machine, Generalized Linear Models and Boosted Regression Tree. Data were collected from feld occurrences and Global Biodiversity Information Facility, and coupled with environment variables selected based on collinearity tests, contribution of variables, and Jackknife tests. We analyzed the main variables afecting their distribution under Representative Concentration Pathways (RCP) 4.5 and RCP 8.5 scenarios by the year 2055. Results showed that Random Forest (RF) was the most appropriate model for predicting the distribution of the three species, with an area under the curve (AUC)>0.90. Cation exchange capacity, isothermality, and potential evapotranspiration are the nvironmental factors that all three species depend on. Under current environmental conditions, P. biglobosa, V. paradoxa, and V. doniana covered 52.10%, 76.91%, and 70.22% of the suitable habitats throughout the study area (11,540 km2). A probable expansion of the suitable habitats was noted, with up to 76.19% for P. biglobosa and 82.82% for V. paradoxa. Exceptionally, V. doniana will lose 7.36% of its suitable habitats under the pessimistic (RCP 8.5) scenarios by the year 2055. These fndings represent a step forward in the process of conserving P. biglobosa, V. paradoxa, and V. doniana in appropriate habitats in the context of climate change.
Keywords: Ecological niche · Climate change · Algorithms · IPCC · Soil fertility · Random Forest